How to Transition Incrementally to Microservice Architecture. - BOZAN, KAROLY; LYYTINEN, KALLE; ROSE, GREGORY M. (Communications of the ACM, 2021)
The article discusses the computer software development framework known as microservice architecture (MSA). It examines how MSA challenges software development organizations (SDOs) during legacy code migration, and provides tips for adapting legacy code to MSA.